Oil extraction from coconut milk by controlled heating - Rosales, Virra Teresa L.; Lizada, Ma. Concepcion C. (2006)
ABSTRACT Heating coconut milk with the use of a water bath resulted in a longer heating time required for the emulsion to break. It also led to a lower oil recovery. The recovery could not be increased by a second extraction of the residue obtained after the first extraction of the coconut cream. The oil obtained by direct heating at 90-95°C had the aroma of "fresh coconut" characteristics of virgin coconut oils and had no visible color. Photomicrographs of the coconut milk emulsion showed that oil globules in the coconut emulsion had diameters ranging from 1.79 i m to 3.2 i m. Disruption of the oil globules at 90-95°C coincided with the coagulation of the proteinaceous mixture, and the separation of the oil. The extracted oil had values for free fatty acid which were lower than that obtained from RBD. Other parameters were within the the standards set by BPS/BAFPS, 2004 (ICS 67.200.10.C) with the exception of the total volatile acids (TVA) values, which were found to be lower than the standards
Thesis (BSFT)--University of the Philippines, Diliman.
Keywords: Coconut oil